1988
DOI: 10.2337/diab.37.6.763
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hypothalamic Neuropeptide Y Concentrations in Diabetic Rat

Abstract: Central and lateral hypothalamic concentrations of 10 regulatory peptides were measured by radioimmunoassay in streptozocin-induced diabetic (STZ-D) and matched control rats between 1 day and 14 wk after diabetes induction. After 2 wk, both central and lateral hypothalamic neuropeptide Y (NPY) concentrations in STZ-D rats were consistently higher than those found in control rats, with significant 30-50% increases at 4 wk in the central hypothalamus, and at 6 and 14 wk in both central and lateral hypothalamus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(26 citation statements)
references
References 35 publications
0
24
0
2
Order By: Relevance
“…This relatively crude dissection technique did not reveal any significant differences between fatty and lean phenotypes, even though the same method had clearly demonstrated raised NPY concentrations in diabetic rats [82,83]. However, subsequent microdissection studies found that NPY concentrations were significantly higher in fatty than in lean Zucker rats in specific regions including the ARC, PVN, DMH and MPO [106,107] (Fig.…”
Section: Could Npy Disturbances Cause Disorders Of Energy Balance?mentioning
confidence: 98%
“…This relatively crude dissection technique did not reveal any significant differences between fatty and lean phenotypes, even though the same method had clearly demonstrated raised NPY concentrations in diabetic rats [82,83]. However, subsequent microdissection studies found that NPY concentrations were significantly higher in fatty than in lean Zucker rats in specific regions including the ARC, PVN, DMH and MPO [106,107] (Fig.…”
Section: Could Npy Disturbances Cause Disorders Of Energy Balance?mentioning
confidence: 98%
“…Williams and colleagues have demonstrated that NPY concentrations in the hypothalamus are significantly increased within 3 weeks of sustained hyperglycaemia in streptozotocin (STZ)-induced diabetic rats, and elevated concentrations of NPY in the hypothalamus in diabetic rats have been suggested to be responsible for diabetic hyperphagia (Williams et al 1988). The present study demonstrates that NPY concentrations in the hypothalamus were also significantly increased following acute hyperglycaemia in rats.…”
Section: Figurementioning
confidence: 99%
“…Neuropeptide Y (NPY), a 36-amino-acid peptide originally isolated from porcine brain, is present in high concentrations in the central nervous system, particularly in the hypothalamus, limbic brain regions, cerebral cortex and various brain stem nuclei (Humphreys et al 1992). NPY concentrations in the central hypothalamus are significantly increased in diabetic rats (Williams et al 1988), and hypoinsulinaemia increases hypothalamic NPY levels (Malabu et al 1992). Alteration of hypothalamic NPY levels, which has potent effects on hypothalamopituitary function (Humphreys et al 1992), may contribute to certain neuroendocrine disturbances in diabetes mellitus.…”
mentioning
confidence: 99%
“…It is well known that in diabetic condition there is an increase in osmolarity that induces thirst by stimulating thirst center in hypothalamus, causing increased water intake and hyperphagia which is followed by polydipsia. Also it may be due to hypothalamic neuropeptide Y (NPY) because previous study reported that concentrations of hypothalamic NPY in diabetic rats were consistently higher than those found in normal control rats, elevated concentrations of NPY, a very potent central stimulant of eating and drinking, may mediate the hyperphagia and polydipsia characteristic of diabetes (Williams et al, 1988;Sipols et al, 1995). Insulin deficiency in diabetes leads to increased hypothalamic AMPK activity, which contributes to the development of diabetic hyperphagia (Namkoong et al, 2005).…”
Section: Discussionmentioning
confidence: 99%